Coffee Intake Reduces Short-Term Carbohydrate and Lipid Consumption - Evgenia Lazou; Ioannis Vlastos; Kalliopi Gkouskou; Efstathios Skoufas; Dimitrios Chaniotis (Dietetics, 2025)
Background: Epidemiological studies on the effect of coffee intake on food consumption have yielded conflicting results. We sought to study the immediate and short-term effects of coffee consumption on food preferences, total calories, and macronutrient consumption within a specific, closely supervised experimental protocol. Methods: Twenty-one normal-weight volunteers completed this crossover, randomized, controlled study. Each volunteer took part in two trials consuming (a) 200 mL of instant coffee providing 5 mg of caffeine/kg body weight or (b) 200 mL of water (control). In both trials, participants were offered an ad libitum lunch meal from a buffet for 30 min. Proteins, lipids, and carbohydrates, as well as total caloric consumption were recorded during the initial 30 min period of the experiment (immediate period) as well as during the rest of the day (short-term period). Results: Coffee intake resulted in a statistically significant lower intake of immediate and short-term carbohydrate consumption (p = 0.012 and p = 0.047), of immediate protein consumption (p = 0.019), and of short-term lipid consumption (p = 0.04) versus water consumption. As a result, the calories consumed both immediately upon coffee administration and during the rest of the day of the experiment were significantly lower (p = 0.026 and p = 0.006) in the coffee group. Conclusions: Coffee intake seems to exert an anorexigenic result that last for several hours upon its consumption, particularly for carbohydrates and lipids.